Maca (Lepidium peruvianum Chacón sp. nov.) and its habitat - Chacon, Gloria (1990)
The author present the taxonomic description of one specimen type of MACA obtained in September 9th, 1989, near Huarancaca, Cerro de Pasco city, Department of Pasco, as Lepidium peruvianum Chacón sp. nov., a new species belonging to the genus Lepidium (Cruciferae), the characteristics that distinguish it from the close species especially from Lepidium meyenii Walp. and Lepidium gelidium Wedd. are detailed in this study. It presents also, a phytochemical study of MACA, made in 1960-1962, its habitat and acclimation at coastal level. This species, whose popular name is MACA, has its origin in the Peruvian Central Andes, where it is known for its nutritional and pharmacological value, domesticated since long before the Incaic period. It grows in the Department of Pasco and Junín, between 4100 and 4300 m over the sea level. The climate is, generally, cold and rather dry in the year, characterized during summer (January, February and March) by an average rainfall of 250.8 mm and a mean temperature of 4.8 °C, while in winter (June, July and August) the rains are sparse, arising to 31.1 mm and with environmental mean temperature of 3.5 °C. The chemical analysis of the root made in 1960 and 1961 showed the presence of glucids and four types of alkaloids in Whatman chromatographic paper. They were designated "Alkaloid extract/March 1961", being them the active principles that are involved in the procreation frequency and the clear and well-marked stimulation of the Graaf follicles maturation in experiments with female rats as well as of an increase in the quantity of spermatozoids in the seminiferous tubes and an augmentation to the mitosis and spermatogony in the males. These assays I have made in the Pathology Institute of the Human Medicine Faculty [of UNMSM] during 1961 and 1962. The histological and histochemical parts made in 1989 and beginning of 1990 in specimen’s brought from Cerro de Pasco, showed that the root of this species present alcaloids and glucids, principles that characterized to the specimen from San Juan de Jarpa and Carhuamayo, Department of Junín, in 1960-1962. It shows at the same time high concentration of Ca, P and Fe, which together with the presence of alkaloids explains the medicinal potential of the plant. There are included 10 tables, 12 diagrams, 94 photos and 4 autopsy protocols.